Data from: Brachiopods from the Byrd Group (Cambrian Series 2, Stage 4), Central Transantarctic Mountains, East Antarctica - Claybourn, Thomas; Skovsted, Christian; Holmer, Lars; Pan, Bing; Myrow, Paul; Topper, Timothy; Brock, Glenn (Zenodo, 2019)
Brachiopods from Cambrian Series 2, Stage 4 carbonate strata of the Byrd Group in the Central Transantarctic Mountains, East Antarctica, are described for the first time. These include six lingulate, one paterinate, and one rhynchonelliform taxa, including the new lingulate brachiopod Plicarmus wildi gen. et sp. nov. The assemblage correlates closely to the brachiopods recently reported from the Xinji Formation (Shuiyu section) in North China, as well as brachiopods recovered from the Dailyatia odyssei Zone across the Arrowie Basin of South Australia. The first unambiguous example of the acrotretid brachiopod Eohadrotreta zhenbaensis Li and Holmer 2004 outside South China is also identified in the context of its ontogenetic stages. Well preserved specimens of the acrotheloid Schizopholis yorkensis (Holmer and Ushatinskaya in Gravestock et al., 2001) facilitates a new reconstruction of its musculature and visceral region. This data is synthesised into a new cladistic analysis that resolves Acrotheloidea as a well-supported monophyletic clade and supports previous notions of a morphocline in acrotheloid evolution. S1 Counts Numbers of dorsal and ventral valves from each fossil-bearing locality S2 Measurements Measurements and summary statistics of valves' morphology S3 List of characters and their states Detield list of characters and character states used in taxon-character metrix S4 Character matrix Detailed character matrix in excel format S5 Character matrix reference list List of references for taxa described in the matrix, where those from published literature are used. S6 Cladistic analysis nexus file Taxa-character matrix in nexus format, used in cladistic analysis S5 Character matrix reference list List of references used for constructing the taxon-character matrix